2020
DOI: 10.1136/vr.m4756
|View full text |Cite
|
Sign up to set email alerts
|

Investigating an outbreak of equine viral arteritis at two connected premises

Abstract: In early 2019, four stallions in the south of England tested positive for equine viral arteritis following routine prebreeding screening. Here, a team from Defra and the APHA describe the epidemiological investigation that was carried out to determine the origin of infection and the potential for its transmission across the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Contact tracing led to the identification of a fourth stallion (FR-I) in a second premise that also tested positive for EAV antibodies and subsequently for EAV in semen. Further epidemiological investigations revealed that the infections must have occurred between April 2018 and April 2019, and that while two stallions (KF-L and KF-P) were imported from Spain in December 2018, it can be excluded that either of these carried the virus to the UK [1]. Virological investigation demonstrated the close relationship between all EAV strains (genotype D), making it likely that one of the stallions (KF-P) had become infected first and spread the virus among his contacts.…”
mentioning
confidence: 99%
“…Contact tracing led to the identification of a fourth stallion (FR-I) in a second premise that also tested positive for EAV antibodies and subsequently for EAV in semen. Further epidemiological investigations revealed that the infections must have occurred between April 2018 and April 2019, and that while two stallions (KF-L and KF-P) were imported from Spain in December 2018, it can be excluded that either of these carried the virus to the UK [1]. Virological investigation demonstrated the close relationship between all EAV strains (genotype D), making it likely that one of the stallions (KF-P) had become infected first and spread the virus among his contacts.…”
mentioning
confidence: 99%